Historical and contemporary aspects of maternal immunity in swine. (10th November 2017) - Poonsuk, Korakrit; Zimmerman, Jeff
Abstract: Maternal immunity plays a pivotal role in swine health and production because piglets are born agammaglobulinemic and with limited cell-mediated immunity, i.e. few peripheral lymphoid cells, immature lymphoid tissues, and no effector and memory T-lymphocytes. Swine do not become fully immunologically competent until about 4 weeks of age, which means that their compromised ability to respond to infectious agents during the first month of life must be supplemented by maternal immune components: (1) circulating antibodies derived from colostrum; (2) mucosal antibodies from colostrum and milk; and (3) immune cells provided in mammary secretions. Because maternal immunity is highly effective at protecting piglets against specific pathogens, strengthening sow herd immunity against certain diseases through exposure or vaccination is a useful management tool for ameliorating clinical effects in piglets and delaying infection until the piglets' immune system is better prepared to respond. In this review, we discuss the anatomy and physiology of lactation, the immune functions of components provided to neonatal swine in mammary secretion, the importance of maternal immunity in the prevention and control of significant pathogens.